Volume 2: Combustion, Fuels and Emissions 2009
DOI: 10.1115/gt2009-60239
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Air-Blast and Flow-Blurring Injectors Using Phase Doppler Particle Analyzer Technique

Abstract: Recent research on biofuels for power generation has typically focused on biodiesel because the biodiesel feedstrock, e.g., vegetable oil, poses significant combustion problems related to poor atomization. Existing injectors cannot effectively atomize high viscosity fuels such as vegetable oil. However, a new, novel flow-blurring (FB) injector concept has shown promise in overcoming the atomization problems. In this study, a FB injector is compared to a commercial air-blast (AB) injector operated with water at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…8 for ALR = 2.5 (Simmons et al 2009;Simmons and Agrawal 2011). 8 for ALR = 2.5 (Simmons et al 2009;Simmons and Agrawal 2011).…”
Section: Spray Characterizationmentioning
confidence: 99%
“…8 for ALR = 2.5 (Simmons et al 2009;Simmons and Agrawal 2011). 8 for ALR = 2.5 (Simmons et al 2009;Simmons and Agrawal 2011).…”
Section: Spray Characterizationmentioning
confidence: 99%
“…Previous studies compared experimentally a flow blurring injector with a commercial airblast injector and showed that the flow blurring injector produces a finer spray than the airblast injector for equivalent conditions, whereas requires lower energy input or lower pressure drop in the atomizing air line [36,37]. Combustion experiments show that for a given equivalence ratio, heat release rate, and atomizing air-to-liquid mass ratio, the flow blurring injector produced three to five times lower NO x and CO emissions in diesel and kerosene flames, compared to the airblast injector [35].…”
Section: Introductionmentioning
confidence: 97%
“…Previous detailed phase Doppler particle analyzer (PDPA) measurements show that the FB injector produces finer spray than that produced by an AB injector at the same atomizing air and liquid mass flow rates. Compared to AB atomizer, the FB injector requires lower energy input since it incurs a lower pressure drop in the atomizing air line [15][16] . For a given overall equivalence ratio, heat release rate (HRR) and atomizing air-to-liquid fuel ratio (ALR), FB atomization in a swirl-stabilized combustor resulted in three to five times lower CO and NOx emissions in diesel and kerosene flames compared to those with AB atomization 17 .…”
Section: Introductionmentioning
confidence: 99%